Large-Scale Deletions of Mitochondrial DNA in Epilepsy Patients Treated with Carbamazepine - Thi Tu Linh, Nguyen; Huong, Vu Thu; Nhan, Le Thi Thanh; Phuong, Le Lan; Thuy, Nguyen Doan; Lieu, Nguyen Van; Anh, Nguyen Thi Van; Thai, Trinh Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1, 2024)
Mitochondrial dysfunction, caused by large-scale deletion mutations, can lead to impaired function of the mitochondrial respiratory chain, reduced ATP production, and serious effects on most energy-consuming organs, such as neurons, and can induce seizures in epilepsy. Carbamazepine (CBZ), the first-line drug used in the treatment of epilepsy, can be harmful to mitochondria and its side effects may be related to mitochondrial dysfunction. In this study, mitochondrial DNA (mtDNA) large-scale deletions were identified in 65 CBZ-treated patients with epilepsy, including 32 patients with CBZ-induced hypersensitivity and 33 with CBZ tolerance. Using the PCR method, mtDNA large-scale deletions were identified in 21/65 epilepsy patients (32.31%), including 9/32 CBZ-hypersensitivity patients (28.13%) and 12/33 CBZ-tolerance patients (36.36%). However, this difference was not statistically significant. The “common deletion” of 4977 bp was the most prevalent deletion. Remarkably, the new deletion of 4876 bp in a CBZ-tolerance patient was reported for the first time. Quantitative PCR analysis showed that the level of mtDNA large-scale deletion was significantly lower in the hypersensitivity group than in the tolerance group (p < 0.05). Besides, analysis of the association between the level of mtDNA large-scale deletion and mtDNA copy number with the clinical features of CBZ hypersensitivity patients showed no relationship with age and severity of skin lesions ( p > 0.05). However, there was a statistically significant association between the level of mtDNA large-scale deletions and sex ( p < 0.01). Further studies are needed to evaluate the role of mtDNA large-scale deletions in epilepsy and their association with antiepileptic drugs.